PEMANFAATAN SOFTWARE GEOGEBRA DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN MATEMATIKA MATERI GEOMETRI BAGI MAHASISWA PGSD UNIVERSITAS MATARAM - Fauzi, Asri; Rahmatih, Aisa Nikmah; Umar; Ermiana, Ida (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2025)
This community service activity aims to improve the ability of Elementary School Teacher Education (PGSD) students in developing mathematics learning media, especially in geometry material, through the use of GeoGebra software. GeoGebra is an interactive software that is very suitable for visualizing geometric concepts dynamically and attractively. In the context of the Independent Curriculum, mastery of educational technology is one of the important competencies that prospective teachers must have, in order to support differentiated, contextual, and student-centered learning. The methods used in this activity include training, direct practice, and mentoring in designing GeoGebra-based learning media. The results of the activity show that students have high enthusiasm in participating in the training, and show an increase in understanding and skills in developing interactive geometry learning media. The media produced also reflects learning principles that are in accordance with the characteristics of elementary school students and support the achievement of the Pancasila student profile. This activity makes a real contribution in preparing prospective teachers who are technology literate and able to design innovative mathematics learning, in line with the demands of the Independent Curriculum.